Physical Geography - Patrich, Jeremy (Open textbook library., 2020)
Welcome to Physical Geography at College of the Canyons. This textbook was designed especially for College of the Canyons students, as a resource to instill the knowledge and adventure that the discipline of geography holds for so many of us. The following units will cover a wide array of topics such as: Earth’s grid system, rivers, oceans, deserts, basic geology, and cartography.